Menabung Dan Berinvestasi: Memahami Dasar-Dasar Literasi Keuangan Untuk Gen Z - Ngadi Permana; Grace Yulianti; Diani Austin (Universitas 45 Surabaya, 2025)
This study aims to examine the level of financial literacy of generation Z related to savings and investment, as well as the importance of understanding both concepts in personal financial management. Generation Z faces challenges in managing their income amidst rapid economic and technological developments. Saving is often considered a safe way to save money with low risk, but is affected by inflation which can reduce purchasing power. On the other hand, investment offers the potential for higher returns but with greater risk. This study uses a qualitative descriptive approach through interviews and surveys involving participants from among students. The results of the study indicate that although generation Z has an interest in investment, many do not understand the fundamental differences between saving and investing and the importance of financial diversification. The recommendation of this study is the importance of financial literacy education that includes understanding risk, financial management, and the use of financial technology in order to achieve long-term financial stability.